Implementasi Metode Regresi Linier Berganda Untuk Proyeksi Kebutuhan Listrik Dalam Rangka Analisis Strategi Bisnis Di PT XYZ - Fadhli Farsa (KILAT, 2019)
Electrical energy requirements in the Industrial Estate should be fulfilled as a supporting industry in the region in order to develop. Therefore, one of PT XYZ's corporate strategies is to do demand forecasting. In this study, the authors will use multiple regression linear methods and compared with Sectoral quantitative forecasting methods from 2018 to 2022. The dependent variable used is the consumption of electrical energy in each sector (industry, business, housing and general) and for independent variables is the total of PT XYZ GDP, Dollar Exchange, PT XA Production, Number of Consumers, Cilegon GRDP, Growth Rate, Contract Power, Cilegon Export & Import, Indonesian Economic Growth. Based on forecasting results using multiple linear regression methods obtained in 2022 the need for electrical energy is 824,252 GWh down by 9.1% from 2017 and compared with the Sectoral quantitative forecasting method 946 GWh increased by 4.3% from 2017, while the average load with the new consumer plan in 2019 - 2021 then the total load in 2022 is 158.61 MW, while the final results from the SWOT analysis show that PT XYZ is in quadrant 1, the strategy is Progressive and in Porter's Five Force's it is found that the average value is 3 which means the industry is still attractive.